Understanding heat and groundwater flow through continental flood basalt provinces: insights gained from alternative models of permeability/depth relationships for the Columbia Plateau, USA. Issue 1 (19th September 2014) - Burns, E. R.; Williams, C. F.; Ingebritsen, S. E.; Voss, C. I.; Spane, F. A.; DeAngelo, J.
Abstract Heat‐flow mapping of the western USA has identified an apparent low‐heat‐flow anomaly coincident with the Columbia Plateau Regional Aquifer System, a thick sequence of basalt aquifers within the Columbia River Basalt Group (CRBG). A heat and mass transport model (SUTRA) was used to evaluate the potential impact of groundwater flow on heat flow along two different regional groundwater flow paths. Limited in situ permeability (k) data from the CRBG are compatible with a steep permeability decrease (approximately 3.5 orders of magnitude) at 600–900 m depth and approximately 40°C. Numerical simulations incorporating this permeability decrease demonstrate that regional groundwater flow can explain lower‐than‐expected heat flow in these highly anisotropic (kx/kz 104) continental flood basalts. Simulation results indicate that the abrupt reduction in permeability at approximately 600 m depth results in an equivalently abrupt transition from a shallow region where heat flow is affected by groundwater flow to a deeper region of conduction‐dominated heat flow. Most existing heat‐flow measurements within the CRBG are from shallower than 600 m depth or near regional groundwater discharge zones, so that heat‐flow maps generated using these data are likely influenced by groundwater flow. Substantial k decreases at similar temperatures have also been observed in the volcanic rocks of the adjacent Cascade Range volcanic arc and at Kilauea Volcano, Hawaii, where they result from low‐temperature hydrothermal alteration.